Chile’s Forests : A Pillar for Inclusive and Sustainable Development - World Bank (Washington, DC: World Bank, 2020)
The economic success of the Chilean forest sector relies heavily on its forest plantations, which are facing significant challenges. Plantations are intensively managed for pulp and other wood products for export. This commercial orientation has promoted voluntary forest management and chain of custody certification and the development and adoption of the Chilean Sustainable Forest Management Certification System (CERTFOR). However, as afforestation rates decline, overall production in forest plantations is falling, which can be explained by lower productivity and management effectiveness of small- and medium-sized forest plantations. Additional challenges include (a) the environmental impact of current management practices, and (b) the possibility of a wood deficit in the coming years. With the focus shifting away from plantations, Chile’s native forests have the potential to provide an increasing range of goods and services. Native forests are generally characterized by unsustainable management practices and thus are highly degraded, often only providing firewood. While considerable research on silvicultural techniques has been conducted, only small areas have adopted sustainable forest management practices, with a focus on thinning of second-growth forests and selective cuttings. However, native forests have the potential to revitalize regional and local economies through more sustainable management systems. For this resource to be sustainably utilized, it is essential to address challenges such as degradation, decapitalization, and poor development of the goods/services market that natural forests generate. Native forests have enormous resilience, and, over time, can recover and build more sustainable production systems, consequently increasing the supply of timber and nontimber resources, as well as biodiversity and other ecosystem services.